Effort Increasing Learning Result Of Communication Operations Calculating Methods Using Napier Bone Students Class Students In Basic Schools 12 Tebat Karai - Lelawarna, Lelawarna (UNIB Press, 2018)
This study aims to determine whether the use of Napier Bone Exam can improve mathematics learning outcomes in multiplication counting operations. The method in this study is a classroom action research with a collaborative form involving researchers who are also as principals, and peers of teachers.This research was conducted in class V at State SDN 12 Tebat Karai District in Kepahiang in the school year 2015/2016 with the number of students 20 people. The focus of this research is the result of mathematics learning on multiplication counting and the effectiveness of napier bone wear. Action Research This class uses two cycles. Each cycle consists of four steps: planning, action, observation and reflection.The results showed an increase, this is evidenced by the results obtained in cycle I and cycle II with SK / KD as well as different indicators in the category of very good. By looking at the results of this study can be concluded that this research is able to answer the purpose of research that the use of napier bone skeleton can improve the results of mathematics learning on the multiplication counts class V students in SDN 12 TebatKaraiKepahiang Regency 2015/2016. Other data relating to research and student work as attached. Finally, researchers suggest to all teachers to be creative in presenting lessons, especially in using props and media that are interesting and varied so that it can bring students in a fun learning process and thorough completion of student learning outcomes can be achieved.